Pengaruh Total Asset Turnover (TATO) dan Working Capital Turnover (WCTO) terhadap Net Profit Margin (NPM) Pada Industri Kosmetik dan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016 - Febry Rumondang Sinaga (Science of Management and Students Research Journal (SMS), 2019)
Net Profit Margin (NPM) is the ratio used to demonstrate a company's ability to generate net profits. Net Profit Margin is the ratio between net income and sales.  All companies in their business activities are profit-oriented, and every company's operations must have an element of cause and what causes the rise and fall of growth of the company, and it can be seen from the development of operating profit. This study aims to know and analyze how the influence of Total Assets Turn Over and Working Capital Turn Over to Net Profit Margin simultaneously and partially on Cosmetic Industry and Household Utilization in Indonesia Stock Exchange Period 2012-2016. The benefits of this research are theoretical and practical benefits. Sample selection method used is purposive sampling. Criteria for sampling research include: (1) Cosmetic and Household Industries listed in Indonesia Stock Exchange (BEI) period 2012-2016; (2) Having a complete financial report during the observation period. Data technique used is multiple linear regression and test of classical assumption. The results of this study indicate that (1) simultaneously Total Assets Turn Over and Working Capital Turn Over significant effect on Net Profit Margin; (2) partial Total Asset Turn Over and Working Capital Turn Over have significant effect to Net Profit Margin. Based on the results of determination coefficient test Net Profit Margin in this study amounted to 44.4% while the remaining 55.6% influenced by other variables outside this study.